DDX5/p68 RNA helicase expression is essential for initiating adipogenesis. Issue 1 (December 2015) - Ramanathan, Nardev; Lim, Nicole; Stewart, Colin
Abstract Background DDX5/p68 RNA helicase is a member of the DEAD (Asp-Glu-Ala-Asp) box proteins. Apart from RNA unwinding, DDX5 is an important transcriptional factor and co-activator in cell proliferation and differentiation. Findings Here, we have characterised the role of DDX5 in adipogenesis in 3T3-L1 cells using siRNA mediated suppression. Transient inhibition ofDdx5 mRNA expression at the start of adipogenesis impairs the differentiation programme even when DDX5 expression is restored later in adipogenesis. However transient suppression ofDdx5 at the later stages of adipogenesis do not impair adipogenesis or triglyceride accumulation suggestingDdx5 expression is dispensable in a mature adipocyte. Conclusion These results implicate DDX5 as a crucial factor involved in the complex transcriptional cascade of events that regulate adipogenesis and essential to the initiation of adipogenesis.